Bioarchaeology and behavior : the people of the ancient Near East - Larsen, Clark Spencer; Perry, Megan A. (Gainesville : University Press of Florida, 2012)
An archaeological exploration of the ancient inhabitants of the circum-Mediterranean region exploring their migration patterns, health, and diet.
1. On the tail end of variation in late Neolithic burial practices: Halaf feasting and cannibalism at Domuztepe, Southeastern Anatolia / Suellen C. Gauld, James S. Oliver, Sarah Whitcher Kansa, Elizabeth Carter -- 2. An exploration of infant burial practices at the site of Kish, Iraq / Christina Torres-Rouff and William J. Pestle -- 3. The burial customs of early Christian Cyprus: a bioarchaeological approach / Sherry C. Fox, Ioanna Moutafi, Eleni Anna Prevedorou, and Despo Pilides -- 4. A bioarchaeological perspective on the burials and basilicas of medieval Polis, Cyprus / Brenda J. Baker and Amy papalexandrou -- 5. Condemned to metallum? Illuminating life at the Byzantine mining camp at Phaeno in Jordan -- Megan A. Perry, Drew S. Coleman, David L. Dettman, and Abdel Halim al-Shiyab -- 6. Food for thought: isotopic evidence for dietary and weaning practices in a Byzantine urban monastery in Jerusalem / Lesley A. Gregoricka and Susan Guise Sheridan -- 7. Buccal dental microwear as an indicator of dietary habits of the Natufian people of el-Wad and el-Kebarah / Mohammad Alrousan and Alejandro Prez-Prez -- 8. Daily activity and lower limb modification at Bab Edh-Dhra{ha}, Jordan, in the early Bronze Age -- Jaime M. Ullinger, Susan G. Sheridan, and Donald J. Ortner.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Human skeleton -- Analysis; Human remains (Archaeology) -- Middle East; Ethnoarchaeology -- Middle East; Excavations (Archaeology) -- Middle East; Middle East -- Antiquities; HISTORY -- Ancient -- General; Antiquities; Ethnoarchaeology; Excavations (Archaeology); Human remains (Archaeology); Human skeleton -- Analysis; Middle East; SOCIAL SCIENCE / Archaeology; Electronic books